The “third digital revolution”: Technologies with human face and anthropological assessment. - Pérez-Latre, Francisco Javier (2022)
Technologies are a wonderful asset, but societies need to be aware of its potential dangers. This article argues the need for anthropological evaluation of ICTs (Information and Communication Technologies). The article is based on an extensive review of classic and recent works about Internet studies, and explores the meaning and human implications of the “digital revolution”. Its goal is to shed light for conceptual thinking about digital environments. It focuses in five areas: what we could call “lonely togetherness”; the value of identity; information overload; community building, and what I will call the “power of the big five”.